A cross sectional study conducted to assess knowledge and awareness regarding HIV/AIDS among attendees of integrated counselling and testing centre at Sagar, Madhya Pradesh - Mishra, Shraddha; Guleri, Sunil K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Acquired immunodeficiency syndrome (AIDS) has emerged as one of most serious public health problem in the country. ICTC (integrated counseling and testing centre) provides a key entry point for the ’continuum of care in HIV/AIDS’ for all segments of the population. This study was conducted to assess knowledge and awareness regarding HIV/AIDS among attendees of ICTC because awareness is only means to reduce prevalence of any disease in absence of availability of treatment and cure. Methods: The study was conducted among attendees of integrated counseling and testing centre who were visited at the centre for HIV testing. It was a cross-sectional, observational study and conducted at ICTC attached to Microbiology Department of Bundelkhand Medical College, Sagar. Results: Majority of study subjects (34.96%) had a relatively poor knowledge about HIV/AIDS. In spite of having awareness, the respondents had lack of complete knowledge about the root cause of HIV/AIDS and had misconceptions about the mode of transmission. Conclusions: Gender, education, residence, caste and socio-economic status showed the significant association with knowledge score regarding HIV/AIDS. IEC activities should be planned in local language incorporating locally derived data pertaining to various social norms, cultural beliefs and sensitivities of community.